Asthma, the central nervous system, and neurocognition: Current findings, potential mechanisms, and treatment implications. (March 2023) - Kroll, Juliet L.; Ritz, Thomas
Abstract: Accumulating behavioral evidence suggests that asthma is associated with cognitive deficits. A number of studies have identified potential biological contributions to cognition in asthma; however, mechanistic pathways of central nervous system (CNS) involvement in asthma are yet to be established. We therefore conducted a literature review to identify studies examining potential CNS contributions to cognition in asthma. In this review, we discuss our general understanding of the CNS in asthma in the context of cognitive performance and outline a working model of mechanistic pathways linking the proposed neural influences of asthma pathology with cognition. To this extent, we incorporate neural, behavioral, psychological, social and environmental factors. Finally, we underscore the clinical significance of the CNS and neurocognitive sequelae in asthma, highlighting potential opportunities for routine monitoring, therapeutic intervention, and recommend key areas for future research. Highlights: Emerging literature supports a role of asthma in the central nervous system structure, function and chemistry. Associations between central nervous system and asthma are likely bidirectional. Achievement of asthma control, may be the most important outcome to benefit the CNS and cognitive performance in patients. Longitudinal study utilizing multiple levels of measurement is urgently needed to provide clarity among findings. Available findings emphasize value of cognitive screening among patients with asthma.